Implementasi Hibah Waris di Kecamatan Bobotsari Kabupaten Purbalingga Perspektif Hukum Waris Islam - Fatorina, Fetri; H, Imam Labib; Fajariyani, Ainun; Ulinnuha, Ulinnuha (Matan : Journal of Islam and Muslim Society, 2025)
Inheritance grants can be used to resolve issues that are not specifically regulated in faraid law or to provide better justice according to individual needs. In some communities, a lack of understanding of the concept of grants and the sharia provisions governing the provision of grants can be an obstacle. Likewise, the implementation of inheritance grants in Bobotsari District has drawn pro and contra. The method of writing this article uses an empirical-normative approach. The nature of this article's research is qualitative. Data is presented using a descriptive-analytical method. Data collection techniques used in this article are using observation, interviews, and documentation. Data analysis in writing this article uses inductive-deductive (effect-cause). The implementation of inheritance grants that occurred in Bobotsari District began with the grantor or heir gathering all members of the nuclear family, consisting of husband or wife and children for a consensus. The process of distributing inheritance grants must fulfill the elements of justice and agreement of the grantees or heirs. The pattern of distribution of inheritance grant assets includes; 1) divided equally; 2) divided based on the closeness of the grantor to the recipient; 3) divided based on the layout of the gift assets. In the view of Islamic inheritance law, this practice applies the concept of takharruj or removing or resigning as an heir.